Pre-Service Teachers’ Integration of Mobile Learning Technologies for Instruction - Kehinde Muritala Nuhu; Nafisat A. Adedokun; Shadrach Omotayo Aderele; Gboyega Ayodeji Aladesusi (Universitas Pendidikan Ganesha, 2022)
The use of mobile devices for learning can broaden the scope of higher education and enable it to reach students better. This study aimed to analyze the integration of pre-service teachers in mobile learning technology for teaching. The population for this study consisted of all pre-service teachers in the metropolis. The Proportional Sampling technique selected 150 respondents based on their estimated population using the Israeli Model. The data collection instrument was an adapted questionnaire. Descriptive and inferential statistics were used to answer research questions and test the proposed hypothesis with product and service solution statistics (SPSS) version 20.0 at a significance level of 0.05. The findings show that pre-service teachers integrate mobile technology for learning at Ilorin university. There are no significant differences in pre-service teacher technology integration for mobile learning by gender. The study concludes that pre-service teachers can improve learning if appropriate mobile technologies are used for learning. Therefore, it is suggested that Pre-service teachers apply mobile technology for learning regardless of their gender.